2011
DOI: 10.51758/agjsr-3/4-2011-0014
|View full text |Cite
|
Sign up to set email alerts
|

Response of Nile Tilapia mono-sex (Oreochromis niloticus) Fingerlings to Different Sources and Levels of Protein Using Garlic and Onion as Feed Phytophytoadditives

Abstract: Twelve experimental diets containing 35% crude protein and 434.29 Kcal gross energy 100g-1 were formulated to process three groups of diets according to protein source and level: group 1 (G1) consists of: 25% fish meal (FM) + 75% soybean meal (SBM); group 2 (G2): 50% FM + 50% SBM and group 3 (G3): 75% FM + 25% SBM. Each group included four treatments according to feed additive source and level: a) control diet (without garlic or onion: D1, D5, D9), b) supplemented with 4% garlic (D2, D6, D10), c) supplemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Several researchers have used Prosopis pods in fish and livestock feed and found that it is a viable alternative to the Mabrouk et al, 2008 high-cost limited available conventional feedstuffs (Table 6). Most investigations on amalgamation of Prosopis pod meal as a fish feed ingredient were conducted on tilapia species.…”
Section: Selected Studies On the Application Of Prosopis Pods In Fish...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have used Prosopis pods in fish and livestock feed and found that it is a viable alternative to the Mabrouk et al, 2008 high-cost limited available conventional feedstuffs (Table 6). Most investigations on amalgamation of Prosopis pod meal as a fish feed ingredient were conducted on tilapia species.…”
Section: Selected Studies On the Application Of Prosopis Pods In Fish...mentioning
confidence: 99%
“…Prosopis pod meal can completely replace the conventional high-cost ingredients (corn meal, wheat flour, rice bran and cottonseed meal) in tilapia feed. The available literature suggests that it may include 6.0 to 38.67% of the feed of tilapia feed with positive impacts on growth and health (Mabrouk et al, 2008;Ramos et al, 2012;Sena et al, 2012;Nascimento et al, 2019). Fermented Prosopis pod can wholly substitute rice bran in the feed of Labeo rohita without impacting growth performance and feed intake (Chovatiya et al, 2016).…”
Section: Selected Studies On the Application Of Prosopis Pods In Fish...mentioning
confidence: 99%
“…Accordingly, functional foods with active components that allow the generation of prophylaxis to prevent infections are an essential tool in the food industry [10,11]. For instance, the salmon industry has incorporated phytoactive elements [12] or special diets to improve the condition of fish against infections by viruses, bacteria, or parasites [13,14]. Immunostimulant compounds that increase the immune response in fish are a new alternative for generating functional food for fish [15].…”
Section: Introductionmentioning
confidence: 99%